Impression of Student Knowledge on Decisions Become a Customer of Islamic Banks - Arniati Arniati; Muryani Arsal; Akhmad Akhmad; Asdar Asdar; Andi Arifwangsa Adiningrat (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2020)
The purpose of the study is to determine the impression / influence of students' knowledge on the decision to become a customer of Islamic banks. This study uses a quantitative descriptive study with pourposiive samples of 50 VII semester students of the Department of Development Economics, Faculty of Economics and Business, Muhammadiyah University, Makassar. Data collection techniques are observation and questionnaires while data analysis techniques are using simple linear regression analysis. The results showed that students' knowledge had a positive and significant effect on the decision to become a customer of a Sharia Bank.